Reversal of diabetes in non-immunosuppressed rhesus macaques by intraportal porcine islet xenografts precedes acute cellular rejection - Kirchhof, Nicole; Shibata, Satoshi; Wijkstrom, Martin; Kulick, David M.; Salerno, Christopher T.; Clemmings, Sue M.; Heremans, Yves; Galili, Uri; Sutherland, David E.R.; Dalmasso, Agustin P.; Hering, Bernhard J. (Xenotransplantation (Københaven), 2004)
:  Background:  The functional response and immunobiology of primarily non‐vascularized islet cell xenografts remain poorly defined in non‐human primates. Methods:  We transplanted 20 000 adult porcine islet equivalents/kg (purified and cultured for 48‐h) intraportally into six streptozotocin‐diabetic and two non‐diabetic rhesus macaques. Two recipients were killed at various intervals post‐transplant for histologic examination of livers bearing xenografts. Results:  Plasma glucose levels in diabetic recipients averaged 94 mg/dl at 12 h, 92 mg/dl at 24 h, 147 mg/dl at 48 h, and 157 mg/dl at 72 h post‐transplant. Serum porcine C‐peptide was present in eight of eight recipients at 12 h, in five of six at 24 h, in four of four at 48 h, and in one of two at 72 h post‐transplant. C3a and SC5b‐9 plasma levels increased at 12 h post‐transplant and returned to pre‐transplant levels by 24 h. IgG, IgM anti‐pig and anti‐Gal IgG serum antibody levels did not increase post‐transplant. Rejection was initiated by IgM and complement deposition on islets. Neutrophils dominated the cellular infiltrate at 12 h; CD4+ and CD8+ T cells were the main infiltrating cells at 24, 48, and 72 h; and macrophages increasingly infiltrated xenografts starting at 24 h post‐transplant. Numerous xenoislets were present at all time points; their proportion without intraislet infiltrates decreased from 65% at 24 h to 17% at 72 h post‐transplant. Conclusions:  Pig‐to‐primate intraportal islet xenografts reverse diabetes and the majority of intraportally transplanted xenogeneic islets are not subject to hyperacute rejection. They undergo acute cellular rejection mediated by CD4+‐ and CD8+ T cells and macrophages.